Reversible Deposition and Stripping of the Cathode Electrolyte Interphase on Li2RuO3 - Hestenes, Julia C.; Ells, Andrew W.; Navarro Goldaraz, Mateo; Sergeyev, Ivan V.; Itin, Boris; Marbella, Lauren E. (Frontiers in Chemistry, 2020)
Performance decline in Li-excess cathodes is generally attributed to structural degradation at the electrode-electrolyte interphase, including transition metal migration into the lithium layer and oxygen evolution into the electrolyte. Reactions between these new surface structures and/or reactive oxygen species in the electrolyte can lead to the formation of a cathode electrolyte interphase (CEI) on the surface of the electrode, though the link between CEI composition and the performance of Li-excess materials is not well understood. To bridge this gap in understanding, we use solid-state nuclear magnetic resonance (SSNMR) spectroscopy, dynamic nuclear polarization (DNP) NMR, and electrochemical impedance spectroscopy (EIS) to assess the chemical composition and resistivity of the CEI on Li2RuO3 as a function of state of charge and cycle number. We show that the CEI that forms on Li2RuO3 when cycled in carbonate-containing electrolytes is similar to the solid electrolyte interphase (SEI) that has been observed on anode materials, containing components such as PEO, Li acetate, carbonates, and LiF. The CEI composition deposited on the cathode surface on charge is chemically distinct from that observed upon discharge, supporting the notion of crosstalk between the SEI and the CEI, with Li+-coordinating species leaving the CEI during delithiation. Migration of the outer CEI combined with the accumulation of poor ionic conducting components on the static inner CEI may contribute to the loss of performance over time in Li-excess cathode materials.